Solving delay differential equations by using implicit 2-point block backward differentiation formula - Heng, S. C.; Ibrahim, Zarina Bibi; Suleiman, Mohamed; Ismail, Fudziah (Universiti Putra Malaysia Press, 2013)
In this paper, an implicit 2-point Block Backward Differentiation formula (BBDF) method was considered for solving Delay Differential Equations (DDEs). The method was implemented by using a constant stepsize via Newton Iteration. This implicit block method was expected to produce two points simultaneously. The efficiency of the method was compared with the existing classical 1-point Backward Differentiation Formula (BDF) in terms of execution time and accuracy